Inverse problem for the interior spectral data of the equation of hydrogen atom - Panakhov, E.S.; Sat, M. (Український математичний журнал, 2012)
We consider the inverse problem for the second-order differential operators with regular singularity and show that the potential function can be uniquely determined by the set of values of eigenfunctions at a certain interior point and parts of two spectra. Розглянуто обернену задачу для диференцiальних операторiв другого порядку з регулярною сингулярнiстю та показано, що потенцiальна функцiя однозначно визначається множиною значень власних функцiй у деякiй внутрiшнiй точцi та частинами двох спектрiв.